Generation Z’s Reliance on UGC and Vlogs For Driving Buying Interest in The Fashion Industry - Irul Juliar Rahman; Fahrezi Rachmayandi; Siska Ernawati Fatimah; Rahmadi Rahmadi (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Generation Z’s frequent engagement with social media platforms significantly shapes their purchasing intentions. They actively use these platforms and tend to trust authentic content, such as reviews and user-shared experiences, more than traditional advertising.Purpose: This study aims to analyze how User-Generated Content (UGC) and vlogs influence Generation Z’s purchasing intentions in the fashion industry, providing insights for businesses to develop effective and authentic marketing strategies.Design/methodology/approach: Using the Slovin formula, 400 respondents were sampled. Data analysis was conducted through Partial Least Squares Structural Equation Modeling (PLS-SEM).Findings/Results: The study reveals that UGC and vlogs affect Generation Z’s purchasing interest by offering personalized, relatable, and interactive content that fosters emotional connections and conveys product information authentically. These findings can guide businesses in refining their marketing strategies for Gen Z.Conclusion: UGC and vlogs moderately influences consumer purchase intentions, emphasizing the importance of authentic, content-driven marketing approaches.Originality/value (State of the art): This article’s contributes originality by examining the combined impact of UGC and vlogs on Gen Z’s purchasing intentions, offering fresh perspectives on effective marketing strategies within the fashion industry. Keywords: UGC (User-Generated Content), vlogs, purchasing intention, Generation Z, fashion industry